FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT IMPLEMENTASI PSAK NO. 109 PADA ORGANISASI PENGELOLA ZAKAT DI KOTA BALIKPAPAN - Selviyana; Wahyu Junaedi (JURNAL AKUNTANSI DAN MANAJEMEN MADANI, 2020)
This research aims to examine the influence of attitudes, subjective norms, behavioralcontrol, and knowledge of PSAK No. 109 on the interest in implementing PSAK No. 109 inthe Zakat management organization in the city of Balikpapan. Independent variables inthis study are attitudes, subjective norms, behavioral control, and knowledge of PSAK No.109. The number of samples studied was 6 samples from the Zakat managementorganization in the city of Balikpapan. The research method used is the quantitativeresearch method and the method of analysis used in this study is to use a descriptiveanalysis with SPSS analysis tool version 20. The results of the hypothesis testing showedthat the subjective norms and knowledge of PSAK No. 109 have a significant positive effecton the interest in the implementation of PSAK No. 109. Meanwhile, the attitude andcontrol of behavior has no positive effect on the interest in the implementation of PSAKNo. 109 at Zakat Management organization in Balikpapan City